Cognitive Enhancement An Interdisciplinary Perspective - Hildt, Elisabeth; Franke, Andreas G. (Trends in Augmentation of Human Performance,, 2013)
Cognitive enhancement is the use of drugs, biotechnological strategies or other means by healthy individuals aiming at the improvement of cognitive functions such as vigilance, concentration or memory without any medical need. In particular, the use of pharmacological substances (caffeine, prescription drugs or illicit drugs) has received considerable attention during the last few years. Currently, however, little is known concerning the use of cognitive enhancers, their effects on healthy individuals and the place and function of cognitive enhancement in everyday life. The purpose of the book is to give an overview of the current research on cognitive enhancement and to provide in-depth insights into the interdisciplinary debate on cognitive enhancement. Authors who stem from various disciplines such as medicine, psychiatry, neuroscience, neurotechnology, philosophy, medical ethics, neuroethics, sports science, social sciences and law contribute to this collected volume which is divided into three sections: Medical and Psychosocial Aspects of Cognitive Enhancement; Philosophical and Ethical Aspects of Cognitive Enhancement; and Sociological, Political and Legal Aspects of Cognitive Enhancement.